The Production of γ-Aminobutyric Acid from Free and Immobilized Cells of Levilactobacillus brevis Cultivated in Anaerobic and Aerobic Conditions - Teresa Zotta; Immacolata Faraone; Marilisa Giavalisco; Eugenio Parente; Ludovica Lela; Livia Vanessa Storti; Annamaria Ricciardi (Microorganisms, 2022)
γ-aminobutyric acid (GABA) has several beneficial effects on human health. GABA may be produced via chemical synthesis or through microbial metabolism, and Levilactobacillus brevis is recognized as a GABA-producing species. In this study, 11 Lvb. brevis strains were screened for GABA production, and the best producers were selected to verify the effect of aerobic (AE) and respiratory (RS) cultivations on growth parameters, biomass, and GABA accumulation. Lvb. brevis LB12 was then used to evaluate the combined effect of the incubation atmosphere (anaerobiosis vs. aerobiosis), cell protection (free vs. immobilized cells), and cell recycling (fresh vs. starved cells) on GABA production. Glutamate (GLU) consumption and GABA accumulation were detected by Thin-layer Chromatography (TLC) and RP-HPLC analyses. The ability to produce GABA was widespread among the strains. AE and RS growth improved biomass production, but oxygen availability impaired GLU to GABA conversion, and the anaerobically growing cells had the highest GABA productivity. Immobilized strains had lower efficiency in both GLU uptake and conversion compared to free cells, probably due to the poor diffusion in alginate beads. The use of resting cells allowed further GABA production without the cultivation step, but cell activity was exhausted after three cycles of reutilization. Lvb. brevis LB12 is an excellent GABA producer, and AE cultivation can be exploited to improve the final cell density; however, the conditions for boosting GLU to GABA conversion and cell regeneration need to be further investigated.